1998
DOI: 10.1161/01.str.29.3.695
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Cerebral Tissue Injury and Perfusion After Temporary Hypoxia-Ischemia in the Rat

Abstract: Background and Purpose-Selective regional sensitivity and delayed damage in cerebral ischemia provide opportunities for directed and late therapy for stroke. Our aim was to characterize the spatial and temporal profile of ischemia-induced changes in cerebral perfusion and tissue status, with the use of noninvasive MRI techniques, to gain more insight in region-specific vulnerability and delayed damage. Methods-Rats underwent 20 minutes of unilateral cerebral hypoxia-ischemia (HI). We performed combined repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
99
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 63 publications
11
99
0
1
Order By: Relevance
“…Our data suggest that the process is more long lasting, leading eventually to severe forms of calcification. In addition to glutamate-driven excitotoxicity, thalamic hypoperfusion and hypometabolism (Dijkhuizen et al, 1998;Barbelivien et al, 2002), which are typical consequences of MCAO, may also contribute to calcification. Hypometabolism in the thalamus leads to reduced energy production, the energy needed to keep calcium at basal cytoplasmic level, and hypoperfusion reduces the pH, which favors precipitation of calcium with phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that the process is more long lasting, leading eventually to severe forms of calcification. In addition to glutamate-driven excitotoxicity, thalamic hypoperfusion and hypometabolism (Dijkhuizen et al, 1998;Barbelivien et al, 2002), which are typical consequences of MCAO, may also contribute to calcification. Hypometabolism in the thalamus leads to reduced energy production, the energy needed to keep calcium at basal cytoplasmic level, and hypoperfusion reduces the pH, which favors precipitation of calcium with phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…10,37,40,41 Twenty-minute occlusion resulted in isolated SNL in two studies, 11,42 whereas a third reported infarction but histological assessment used silver impregnation only. 43 Finally, all studies assessing p15-minute occlusions reported isolated SNL, 10,11,35,37,40 except in Zhan et al 38 where microinfarcts with as short as 5-minute tMCAo were reported; however, their definition for 'microinfarct' in fact probably refers to patchy SNL. 15 Importantly, the severity of striatal SNL clearly increases with longer occlusion times, from B5% up to B20% between 10-and 20-minute MCAo.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Even though T 1 -w and T 2 -w MRI have been shown to closely reflect the extent of irreversibly damaged tissue in the past, there is evidence that this correlation will not always hold in certain brain regions and at later time points (Knight et al, 1994;Neumann-Haefelin et al, 2000). Paramagnetic properties of inflammatory cells or blood degradation products, as well as regionspecific changes in water content and breakdown of macromolecular structures with influence on relaxation times, have been discussed as possible reasons for this phenomenon (Dijkhuizen et al, 1998;Lin et al, 2002a). Our own analysis showed a time-dependent accumulation of iron-containing macrophages in the region around leaky blood vessels, which led to selective T 2 * sensitivity without any influence on either T 1 or T 2 detectable at 10 weeks after MCAO (Hoehn et al, 2004;Weber et al, 2005).…”
Section: Lesion Developmentmentioning
confidence: 99%